A Neurologist's View of Lyme Disease and Other Tick-Borne Infections - Halperin, John J. (Seminars in Neurology, 2019)
Tick-borne infections—including tick-borne encephalitis viruses, represented in the United States by rare infections with Powassan and deer tick viruses, and more often Lyme disease—are of increasing importance to neurologists. Lyme neuroborreliosis (LNB) causes all or part of a triad including meningitis, radiculoneuritis, and cranial neuritis. Rarely, parenchymal brain and spinal cord involvement occur, with focal findings on examination and magnetic resonance imaging (MRI). LNB diagnosis requires plausible exposure, objective evidence of nervous system involvement, and, generally, positive two-tier serology. Central nervous system (CNS) LNB is almost always accompanied by abnormal cerebrospinal fluid (CSF) (cells, protein), often with intrathecal antibody production, which is determined by concentration-adjusted comparison of serum and CSF antibody. Measuring CSF antibody in isolation and nucleic acid-based testing of CSF are not useful in LNB and should be avoided. LNB treatment is highly effective with a 2- to 3-week course of antibiotics. Increasing evidence suggests that LNB not involving the CNS parenchyma can be treated successfully with oral doxycycline.
Keywords: Lyme disease; Borrelia burgdorferi; neuroborreliosis; neurologic; nervous system; diagnosis; treatment; Powassan; Borrelia mayonii; Borrelia miyamotoi